PENGEMBANGAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATA PELAJARAN FIQIH - Rosady, Imron; Dahlan, Moh; Ubaidillah, Ubaidillah (Kwangsan: Jurnal Teknologi Pendidikan, 2023)
The purpose of this research is to develop a valid, practical, and effective Contextual Teaching and Learning (CTL) model for the subject of Fiqh (Islamic Jurisprudence). This study refers to the general problem-solving model in education proposed by Plomp, which consists of four stages: (1) initial investigation, (2) design, (3) realization/construction, and (4) testing, evaluation, and revision. However, the implementation stage was not carried out in this research as the development of the learning model did not reach that stage. The research results indicate that in the first experiment, there was an improvement in students' thinking skills at the level of Fiqh 5 by 20.8% and 38.9%, with a decrease of 6.3% and 21.1% in groups A-B and C-D, respectively. In the second experiment, the students' thinking skills at the level of Fiqh 5 increased by 26.0% and 36.8% in groups A-B and C-D, respectively, with a decrease of 8.3% and 11.6%. CTL successfully improved students' thinking skills in Fiqh, although it has not reached its full potential. The increase in students' thinking skills from the first to the second experiment was 29.8% and 31.4%, with a decrease of 14.7% and 9.9%. This can be interpreted as the students' experiences gained through CTL-based learning contributing to the improvement of their thinking skills.AbstrakTujuan penelitian ini mengembangankan model pembelajaran CTL pada mata pelajaran Fiqh secara valid, praktis dan efektif. Penelitian ini mengacu pada model umum penyelesaian masalah pendidikan yang dikemukakan oleh Plomp, tahapan pengembangan model Plomp meliputi (1) investigasi awal, (2) desain, (3) realisasi/konstruksi, dan (4) tahap pelaksanaan tes, evaluasi, dan revisi. Namun, tahap implementasi tidak dilakukan dalam penelitian ini karena pengembangan model pembelajaran tidak sampai pada tahap tersebut. Hasil penelitian Hasil percobaan pertama menunjukkan peningkatan tingkat berpikir siswa pada tingkat 5 Fiqh sebesar 20,8% dan 38,9%, dengan penurunan 6,3% dan 21,1% pada kelompok A-B dan C-D. Percobaan kedua meningkatkan tingkat berpikir siswa pada tingkat 5 Fiqh kelompok A-B dan C-D masing-masing sebesar 26,0% dan 36,8%, dengan penurunan 8,3% dan 11,6%. CTL berhasil meningkatkan tingkat berpikir siswa dalam Fiqh meskipun belum optimal. Peningkatan tingkat berpikir siswa dari percobaan pertama ke kedua adalah 29,8% dan 31,4%, dengan penurunan 14,7% dan 9,9%. Hal ini dapat diinterpretasikan bahwa pengalaman siswa yang diperoleh melalui pembelajaran menggunakan CTL berkontribusi pada peningkatan tingkat berpikir siswa.